2006
DOI: 10.1128/mcb.02341-05
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Role for Sphingosine Kinase 1 in Intestinal Adenoma Cell Proliferation

Abstract: Sphingosine kinase (Sphk) enzymes are important in intracellular sphingolipid metabolism as well as in the biosynthesis of sphingosine 1-phosphate (S1P), an extracellular lipid mediator. Here, we show that Sphk1 is expressed and is required for small intestinal tumor cell proliferation in Apc Min/؉ mice. Adenoma size but not incidence was dramatically reduced in Apc Min/؉ Sphk ؊/؊ mice. Concomitantly, epithelial cell proliferation in the polyps was significantly attenuated, suggesting that Sphk1 regulates aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
175
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(182 citation statements)
references
References 41 publications
7
175
0
Order By: Relevance
“…[79][80][81][82][83] A recent study demonstrated that Sphk1, the major enzyme necessary for synthesizing S1P, is required for enlargement of Min mouse adenomas, since Min mice that do not express this enzyme develop only small adenomas, in contrast to the significant number of large adenomas that developed in Min mice with intact Sphk1 expression. 84 Importantly, both S1P and sphingosine levels were high in Min mouse polyps compared to normal adjacent tissues, indicating that sphingolipid metabolism is abnormal in the neoplastic tissue. When we subsequently quantitated SPL expression in Min mouse adenomas and normal intestinal epithelium by immunohistochemistry and western blotting, we found SPL expression to be high in the intestinal villi, as expected.…”
Section: S1p Lyase Sownregulation In Intestinal Tumorigenesismentioning
confidence: 99%
“…[79][80][81][82][83] A recent study demonstrated that Sphk1, the major enzyme necessary for synthesizing S1P, is required for enlargement of Min mouse adenomas, since Min mice that do not express this enzyme develop only small adenomas, in contrast to the significant number of large adenomas that developed in Min mice with intact Sphk1 expression. 84 Importantly, both S1P and sphingosine levels were high in Min mouse polyps compared to normal adjacent tissues, indicating that sphingolipid metabolism is abnormal in the neoplastic tissue. When we subsequently quantitated SPL expression in Min mouse adenomas and normal intestinal epithelium by immunohistochemistry and western blotting, we found SPL expression to be high in the intestinal villi, as expected.…”
Section: S1p Lyase Sownregulation In Intestinal Tumorigenesismentioning
confidence: 99%
“…SK1 has a crucial role in determining the cellular balance of pro-apoptotic ceramide and sphingosine and pro-proliferative, pro-survival S1P, and there is now substantial evidence that SK1 has a role in tumourigenesis (Cuvillier, 2008). For example, SK1 expression is elevated in a variety of human solid tumours (French et al, 2003), overexpression of SK1 in NIH 3T3 fibroblasts leads to their neoplastic transformation , chemical inhibition or genetic ablation of SK1 reduces tumour growth in vivo (French et al, 2003;Kohno et al, 2006;Kawamori et al, 2009) and SK inhibitors or a dominant-negative SK1 can reduce neoplastic cell transformation induced by oncogenic H-Ras .…”
Section: Introductionmentioning
confidence: 99%
“…SPHK1 overexpression results in oncogenic transformation of normal fibroblasts (15,16), whereas the absence of SPHK1 in mice protects against the development of colon adenomas (17,18). Up-regulation of SPHK1 has been observed in many different tumors, including breast (19,20), lung (21,22), colon (17,18), and glioma (23,24), and increased SPHK1 expression has been associated with a poor survival outcome in GBM (24) as well as breast (20) and lung cancer (22). This has made SPHK1 a target of interest in cancer for biotechnology and pharmaceutical companies.…”
mentioning
confidence: 99%